Why is there change in travel behaviour? In search of a theoretical framework for mobility biographies - Scheiner, Joachim (ERDKUNDE, 2018)
In the past decade, life course approaches to travel have emerged that seek to understand the dynamics of travel behaviour over the life course. While this concept, often labelled ‘mobility biographies’, has generated a multitude of studies, it still lacks theoretical underpinning. This paper discusses key concepts drawn primarily from psychology and sociology that may help understand the mechanisms that contribute to stability and change in travel behaviour. Specifically, it discusses levels of change and stability (ranging between the individual and ‘the system’), factors that serve resistance to change (habits, heuristics, personalities, and regimes), factors that trigger change (such as changed requirements, opportunities, or abilities; motivation; the interplay between attitudes and context; stress; expected outcome of change), stages of behavioural change, and the role of socialisation in stability and change. The paper concludes with an outline of research needs. This includes making stronger links between qualitative and quantitative approaches, linking mobility biographies with research on the social embedding of travel, looking at interactions between life domains, behavioural dimensions, and population groups, and the further development of policy approaches.